HETEROSIS, HETEROBELTIOSIS DAN TINDAK GEN KARAKTER AGRONOMIK KEDELAI {Glycine max (L.) Merrill} - Ayda Krisnawati; MM Adie (BERITA BIOLOGI, 2011)
Most of the soybean {Gfycine max (L.) Merrill (varieties in Indonesia are produced through hybridization. Expected value of heterobeltiosis,heterosis and the gene action is needed to know to optimize the development strategy of soybean varieties. The experiment was conducted in The Balai Penelitian Tanaman Kacang-kacangan dan Umbi-umbian (Balitkabi) greenhouse. The first stage was to form Fl hybrid seed,which was done from May to July 2009; the second stage was for the assessment of Fl plants (August-November 2009). Heterosis,heterobeltiosis and the potential ratio are calculated from the 18 crosses combinations derived from 6 parental genotypes. Data used include the flowering day (days), maturity day (days), plant height (cm), number of branches/plant, number of node/plant, number of pods/plant,seed yield/plant (g) and SO seeds weight (g). Cross combinations that have the highest heterosis values are on the flowering day, maturity day, number of branches/plant and number of node/plant; heterobeltiosis also showed the highest value on the same agronomic characters.Heterosis value of the character of seeds per plant ranged from -36.50% to 75.49%, while for heterobeltiosis ranged from -48.68% to 58.31%. The highest heterosis value was indicated by the Fl from crosses Willis x Malabar. The highest heterobeltiosis value was indicated by crosses of Willis x Grobogan, which means that these crosses have the 58.31% higher yield than the best parents. The soybean yield is controlled by dominant genes and over-dominant. Combination crosses Willis X MLG 0706 (reciprocal) has a higher potential ratio for die character of the number of pods and seeds yield/plant compared to the value of the other potence ratio. Development of soybeans with the use of hybrid heterosis phenomenon still needs to be assessed in terms of economic feasibility.